2021
DOI: 10.1002/hyp.14284
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient source attribution: Quantitative typology distinction of active and legacy source contributions to waterborne loads

Abstract: Distinction between active and legacy sources of nutrients is needed for effective reduction of waterborne nutrient loads and associated eutrophication. This study quantifies main typological differences in nutrient load behaviour versus water discharge for active and legacy sources. This quantitative typology is used for source attribution based on monitoring data for water discharge and concentrations of total nitrogen (TN) and total phosphorous (TP) from 37 catchments draining into the Baltic Sea along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Furthermore, quality‐focused studies could be expected to more frequently address both flow‐quality and storage‐quality linkages. For example, large‐scale nutrient and pollutant loads from subsurface legacy nutrients and pollutants are found to be important for surface and coastal water quality (Basu et al., 2022; Sharpley et al., 2013) and shown to be largely determined by flow variability and change (Cantoni et al., 2023; Chen et al., 2021; Destouni et al., 2021). Moreover, even relatively small groundwater level rise (i.e., storage increase) has been found to drive water quality deterioration by mobilizing pollutants residing in topsoil and increasing colloidal pollutant transport (Jarsjö et al., 2020).…”
Section: Discussion Of Research Gaps and Prioritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, quality‐focused studies could be expected to more frequently address both flow‐quality and storage‐quality linkages. For example, large‐scale nutrient and pollutant loads from subsurface legacy nutrients and pollutants are found to be important for surface and coastal water quality (Basu et al., 2022; Sharpley et al., 2013) and shown to be largely determined by flow variability and change (Cantoni et al., 2023; Chen et al., 2021; Destouni et al., 2021). Moreover, even relatively small groundwater level rise (i.e., storage increase) has been found to drive water quality deterioration by mobilizing pollutants residing in topsoil and increasing colloidal pollutant transport (Jarsjö et al., 2020).…”
Section: Discussion Of Research Gaps and Prioritiesmentioning
confidence: 99%
“…The former finding is reasonable considering that nutrient and pollutant loads carried by terrestrial water to coastal waters are essential for coastal water quality (Lithgow et al., 2017; Van Koningsveld et al., 2003; Vigouroux & Destouni, 2022). However, as discussed above, large‐scale GSW flow and storage conditions are also essential in driving major nutrient and pollutant loads from land to sea (Cantoni et al., 2023; Chen et al., 2021; Jarsjö et al., 2020). The lacking consideration of coastal linkages in large‐scale flow and storage papers thus combines with the lack of studies considering the large‐scale quality‐flow and quality‐storage coupling in emphasizing essential gaps and priorities to advance knowledge about these large‐scale interactions in future research.…”
Section: Discussion Of Research Gaps and Prioritiesmentioning
confidence: 99%
“…A model of a 500 km 2 watershed in Iowa indicated that, following a total cessation of fertilizer application, a 50% reduction in streamwater nitrate could be achieved in 1 year in the scenario without N legacies but would take 19 years with N legacies (Ilampooranan et al 2019 ). Legacy nutrient inputs may be contributing to minimal water quality improvements in the Chesapeake Bay (Chang et al 2021 ; Stephenson et al 2021 ), Mississippi River Basin (Van Meter et al 2017 ), and catchments draining into the Baltic Sea (Chen et al 2021 ), despite significant efforts to reduce nutrient inputs to these waterbodies. If nutrient concentrations are controlled by legacy inputs across the US, resulting lags in water quality improvement will mask or dampen positive effects of nonpoint source pollution provisions in the CWA.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty represents heterogeneity in hydrogeochemical processes during the sampling events and heterogeneity in nitrogen initial distribution as legacy source of nitrogen. Such uncertainty could be reduced with more observations that reflect the spatial and temporal variation of the nitrogen export, with the capability to quantify the proportion of active and legacy source of nitrogen, which is important in managing effective water quality improvement of downstream environment (Basu et al., 2022; Chen et al., 2021).…”
Section: Discussionmentioning
confidence: 99%